Match between dimensions of classroom desk and chair and anthropometric data of primary school students: A case study of a school in Songkhla - Kulem, Rattana; Pochana, Klangduen; Sungkhapong, Angoon (Engineering and Applied Science Research, 2015)
The aim of this study was to compare percent match of furniture sizes with the anthropometric characteristics of primary students. The sample consisted of 360 students (175 male, 185 female). The anthropometric characteristics of students were measured with a portable anthropometer. Eight anthropometric measures and six dimensions of desks and chairs were measured. The anthropometric measures of the students and the furniture dimensions were compared by considering the ergonomic principles in order to identify any incompatibility between them. According to the evaluation, it can be concluded that seat height (SH), seat to desk height (SDH), seat depth (SD), upper edge of backrest (UEB), seat to desk clearance (SDC), and seat width (SW) of the classroom furniture matched to the student’s anthropometric characteristics with 3.61% 5.57% 15.56% 36.72% 81.02% and 98.08%, respectively. The furniture dimensions were recommended ergonomically in order to increase percentage match. With new proposed dimensions, it resulted in increasing of percentage match of SH, SDH, SD, UEB, SDC and SW to 66.48% 65.64% 62.68% 100% 98.52% และ 99.52%, respectively. The results of this study highlight the fact that the dimensions of existing classroom furniture should be redesigned based on ergonomics concern in order to decrease a level of mismatch which may result in anatomical problem of students in future.